Spin Dynamics in Confined Magnetic Structures III - Hillebrands, Burkard; Thiaville, Andre (Topics in Applied Physics,, 2006)
This third volume of Spin Dynamics in Confined Magnetic Structures addresses central aspects of spin-dynamic phenomena, including recent new developments, on a tutorial level. Researchers will find a comprehensive compilation of the current work in the field. Introductory chapters help newcomers to understand the basic concepts. The more advanced chapters give the current state of the art of spin dynamic issues ranging from the femtosecond to the microsecond regime. This volume concentrates on new experimental techniques such as ferromagnetic-resonance-force microscopy and two-photon photoemission, as well as on aspects of precessional switching, spin-wave excitation, vortex dynamics, spin relaxation, domain-wall dynamics in nanowires and their applications to magnetic logic devices. An important chapter is devoted to the presently very hot subject of the spin-transfer torque, combining the physics of electronic transport and micromagnetics. The comprehensive presentation of these developments makes this volume a very timely and valuable resource for every researcher working in the field of magnetism.